Fetal Brain MRI: Novel Classification and Contribution to Sonography - Gat, I.; Hoffmann, C.; Shashar, D.; Yosef, O. B.; Konen, E.; Achiron, R.; Brandt, B.; Katorza, E. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: 1) To evaluate and classify the indications for fetal brain MRI in a tertiary referral center. 2) To assess the contribution of fetal brain MRI to fetal neurosonography.Materials and Methods: A retrospective study in a tertiary medical center during a two-year period (2011 – 2012) included pregnant women who underwent fetal brain MRI. MRI was implemented at 32 weeks of gestation unless a severe abnormality possibly requiring earlier medical intervention was suspected.Results: 633 patients were included, 40 (6.3 %) underwent repeated examinations with a total of 733 fetal MRI scans. Patients were classified to three main indication cohorts: Suspected primary brain anomaly (52.9 %), non-CNS disorders (32.5 %) and obstetrical complications (14.6 %). These cohorts were further divided into 16 separate groups with lateral ventricle abnormalities being the most common (23.7 %), followed by exposure to TORCH (17.5 %) and cerebral cortex abnormalities (13 %). 149 (19.3 %) fetal MRI scans demonstrated additional findings. Repeated examinations were commonly implemented in complicated monochorionic-biamniotic (MCBA) twin pregnancies (34.6 %) and in cases of supra-tentorial cysts (19 %). The average gestational age for MRI scan in the MCBA group was 26 ± 5 weeks in comparison to ≥ 31st weeks in all other groups (p < 0.001).Conclusion: The current study describes a detailed picture of fetal brain MRI indications. Most patients were referred because of CNS anomalies. The impressive diversity of 16 separate entities emphasizes the expanding use of fetal brain MRI. Complicated MCBA pregnancies, which may have dramatic events, constitute a unique challenge due to early and repetitive MRI examinations and may serve as a role model for the contribution of fetal MRI during antenatal evaluation. The contribution of MRI to prenatal evaluation in various indications is discussed.
Keywords: brain; CNS; MR imaging